2001
DOI: 10.1063/1.1420071
|View full text |Cite
|
Sign up to set email alerts
|

Structural (n, m) determination of isolated single wall carbon nanotubes by resonant Raman scattering

Abstract: We show that the Raman scattering technique can give complete structural information for onedimensional systems, such as carbon nanotubes. Resonant confocal micro-Raman spectroscopy of an ͑n, m͒ individual single-wall nanotube makes it possible to assign its chirality uniquely by measuring one radial breathing mode frequency v RBM and using the theory of resonant transitions. A unique chirality assignment can be made for both metallic and semiconducting nanotubes of diameter d t , using the parameters g 0 2.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
184
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(196 citation statements)
references
References 1 publication
10
184
1
1
Order By: Relevance
“…Raman signals of SWNTs have been studied intensively in the literature (see e.g. Duesberg et al , 2000; Jorio et al , 2001; Yu & Brus, 2001; Maultzsch et al , 2002) and signal enhancements of up to 10 12 have been reported for tubes in contact with fractal silver colloidal clusters (Kneipp et al , 2000).…”
Section: Introductionmentioning
confidence: 65%
“…Raman signals of SWNTs have been studied intensively in the literature (see e.g. Duesberg et al , 2000; Jorio et al , 2001; Yu & Brus, 2001; Maultzsch et al , 2002) and signal enhancements of up to 10 12 have been reported for tubes in contact with fractal silver colloidal clusters (Kneipp et al , 2000).…”
Section: Introductionmentioning
confidence: 65%
“…There at two types of CNT: single-walled (SWCNT) and multi-walled (MWCNT). SWCNT are a single tube of graphene with a diameter ranging from 0.4-3.0 nm and a length up to 1 μm [57, 58]. MWCNT are multiple layers of tubes stacking within each other with an overall diameter of 1.4-100 nm and can be up to several microns long [58].…”
Section: In Vivo Toxicity Of Nanomaterialsmentioning
confidence: 99%
“…Single walled CNT have typically fibre-like dimensions with diameters of 0.7-3 nm (Jorio et al 2001) and a length of up to 100 mm. Multi-walled CNT (MWCNT) consist of several layers of carbon cylinders, which increases diameter to10-200 nm (Hou et al 2003).…”
Section: Introductionmentioning
confidence: 99%